Processing of ceramic composite coating via TIG torch welding technique - Bello, Kamilu Adeyemi; Maleque, Md. Abdul; Adebisi, Adetayo A. (Elsevier Inc., 2020)
Advances in materials performance undoubtedly require the development of composite systems, of which coated materials are one form. The formation of ceramic composite coatings on various metallic surfaces for wear resistant applications has witnessed a surge in interest among researchers in tribology community. Today, arc heat sources from welding process are largely used as the means for processing composite coatings. Tungsten inert gas (TIG) heating source has shown a huge potential to be used for composite coating of metallic materials as the process is simpler, cost effective and a flexible when compared with the conventional laser cladding. In the recent years, the quest for cheaper and functional coating solutions has led many researchers to explore possibility of developing newer variant of composite coatings via TIG torch welding process. However, very limited scientific information is available pertaining to the preparation of surface composite coatings by this process and this, therefore, deserves a thorough and exhaustive study. After a brief review of surface engineering and ceramic coating system, this paper discusses in detail about TIG torch composite coating technology, coating deposition mechanism, preparation and their characterization including microstructural features and tribological properties.